Validation of Multi Residue Method with Mixture of Multi-Class Pesticides in Bitter Gourd by Gas Chromatography Coupled with Triple Quadrupole Mass Spectrometry - Raveendranath, D.; Sri Rama Murthy, K.; Harinatha Reddy, A.; Uma, A.; Vijayalakshmi, B.; Ramesh, B. (Asian Journal of Chemistry, 2015)
A new multi-residue method has been developed and validated for the routine analysis of 64 multi-class pesticide residues in bitter gourd (Momordica charantia L.) by gas chromatography coupled with triple quadrupole mass spectrometry in a single run of 49.67 min. The method was successfully applied for the analysis 10 varieties of cucurbits (ash gourd, bitter gourd, little gourd, cucumber, ridge gourd, bottle gourd, snake gourd, water melon, gherkin and pumpkin). Samples were extracted by the application of a single phase extraction of 15 g of sample with 30 mL of acetonitrile, followed by a liquid-liquid partition formed by the addition of 1.2 g of MgSO4. A dispersive solid-phase extraction with 0.4 g of primary secondary amine (PSA) was applied to clean up the extract. The method was properly validated and the values of some merit figures, such as recovery, precision, linearity, detection limit and quantification limit for each pesticide were calculated. The average recoveries in bitter gourd obtained for each pesticide ranged between 70-130 % at three fortification levels (0.01, 0.05 and 0.1 mg kg-1). The percentage of relative standard deviation (% RSD) is lower than the 20 %. The established limit of detection (LOD) is 0.001 mg kg-1 and limit of quantification were (LOQ) 0.01 mg kg-1.